Pemanfaatan Media Sosial Bagi Volume Penjualan Produk Skincare Dan Kosmetik Derr Cosmetics - Elisa Febriani; Ifa Aulia Mariska; Muhammad Farras Nasrida (Pusat Riset dan Inovasi Nasional, 2023)
Technology that is increasingly becoming more developed and advanced makes people's activities easier. Internet technology that is increasingly sophisticated gives birth to social media that at this time cannot be separated from our lives. Social media has a positive impact on society, especially for those who have businesses. Social media is currently widely used by business people to market the products they sell. Derr Cosmetics is one of the sales businesses in the field of skincare and cosmetics located in Palangka Raya, Central Kalimantan which participates in utilizing social media to market its products. By utilizing social media in marketing its products, Derr Cosmetics managed to increase its sales volume to be larger and have many customers.